Architectural modelmaking - Dunn, Nick. (Portfolio skills. Architecture, 2010)
The physical scale model is often cited as an important tool of communication for architecture students and practitioners alike. This book focuses on the inspiring possibilities for modelling the built environment with all the different media and techniques that are now available.